From Exploration to Fixation: An Integrative View of Yarbus's Vision. (August 2015) - Martinez-Conde, Susana; Macknik, Stephen L.
Alfred Lukyanovich Yarbus (1914–1986) pioneered the study of stabilized retinal images, miniature eye movements, and the cognitive influences that act on visual scanning. Yarbus's studies of these different topics have remained fundamentally disconnected and independent of each other, however. In this review, we propose that Yarbus's various research lines are instead deeply and intrinsically interconnected, as are the small eye movements produced during visual fixation and the large-scale scanning patterns associated with visual exploration of objects and scenes. Such apparently disparate viewing behaviors may represent the extremes of a single continuum of oculomotor performance that operates across spatial scales when we search the visual world.